GRAND PREANGER BANDUNG EFFECTIVE MARKETING COMMUNICATION STRATEGY IN THE STAYCATION PROGRAM - Ismunandar Ismunandar; Neneng Yanti Andriani; Rianda Hanis; Ramadhani Hamzah; Muhammad Yusuf (Jurnal Ekonomi, 2023)
This research focuses on the Grand Preanger Hotel's branding strategy for staycation activities and the effective use of marketing communication tactics. As a result of the Covid-19 outbreak in Indonesia, everyone must take health precautions and exhibit caution when performing various tasks. People prefer staycation activities to traditional vacations. Because people feel safer, the Covid-19 virus can spread less. As informants, the Grand Tryas Hotel's branding consultant, marketing manager, and executive assistant manager took part in the study. A qualitative descriptive method as well as an interpretive paradigm are used in this work. The triangulation method is used in the data validation strategy. Theoretical frameworks for branding, marketing communications theory, and effective marketing communication tactics are all employed. Grand Preanger Hotel considers the audience's needs for staycation activities throughout the strategic planning process. to meet the audience's expectations and persuade them to participate in staycation activities at the Grand Tryas Hotel. Grand Preanger Hotel employs a message plan and a media strategy throughout the implementation stage in order to meet the objectives of the staycation activity branding campaign. Grand Preanger Hotel uses feedback, request, and offer messages, as well as corrective action, to fix problems made during the strategy review step. They also increase the possibilities and chances for newly developed techniques.